LANGUAGE, IDEOLOGY, AND POLICY: A CRITICAL DISCOURSE ANALYSIS OF MEDIA REPRESENTATIONS OF THE MERDEKA CURRICULUM IN INDONESIA - Muhammad Fahri Jaya Sudding; Ahmad Azhari; Citra Dwi Safitri (J-Shelves of Indragiri (JSI), 2026)
Educational reform is frequently shaped and contested through media discourse, where language plays a significant role in constructing public understanding, ideology, and policy narratives. This study investigates how Indonesian media construct and negotiate discourse on the Merdeka Curriculum through the interplay of language, ideology, and policy. Drawing on Critical Discourse Analysis based on Norman Fairclough’s three-dimensional framework, this research examines ten online news articles published between 2023 and 2025 across diverse media platforms, including Detik.com, Kompas.id, Kompasiana, CNN Indonesia, and Tempo.co. The study adopts a qualitative approach using document analysis to explore linguistic features, discursive practices, and socio-cultural contexts embedded in media texts. The findings reveal that media representations of the Merdeka Curriculum are constructed through three dominant discursive patterns: critical discourse, optimistic discourse, and institutional discourse. At the textual level, these patterns are reflected in the use of evaluative language, modality, and lexical choices that position the policy as problematic, transformative, or managerial. At the level of discursive practice, differences in framing strategies across media platforms demonstrate how narratives are shaped by institutional roles and communicative purposes. At the level of social practice, the coexistence of these discourses reflects ongoing ideological negotiation related to educational reform, governance, and social equity in Indonesia. This study argues that media discourse does not merely represent educational policy but actively contributes to its construction and legitimation. By integrating language, ideology, and policy within a unified analytical framework, this research contributes to the field of Applied Linguistics and discourse studies, particularly in the context of the Global South. The findings also highlight the importance of critically engaging with media narratives in understanding the dynamics of educational reform.